Pengaruh Latihan Hatha Yoga Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi di Wilayah Puskesmas Kendalsari Kota Malang - imam subekti; Diah Ajeng Pertiwi; Lenni Saragih (Poltekkes Kemenkes Malang, 2022)
Hypertension in the elderly is an increase in systolic blood pressure 160 mmHg and diastolic pressure 90 mmHg. There are several factors that influence the increase in blood pressure in the elderly, including age and lifestyle factors. Handling hypertension can bee done with non-pharmacological therapy, one of which is hatha yoga exercise. The purpose of this research was to know the effect of yoga exercise on reducing blood pressure in the elderly with hypertension in the area Kendalsari Public Health Center, Malang City. The research methods uses a descriptive case study involving 1 elderly person who suffers from hypertension. The instrument in this research used interviews and observation. The data were analyzed qualitatively inductively and presented in the form of tables and naratives. The results of observations that have been carried out show that the systolic and diastolic pressures after yoga are 151.70 mmHg and 86.08 mmHg. There was a decrease of 4.94 mmHg for systolic blood pressure and 7.83 mmHg for diastolic blood pressure. Based on the results of research that has been done, it is concluded that there is an effect of yoga exercise on reducing blood pressure elderly patients with hypertension.